Deep learning in rib fracture imaging: study quality assessment using the Must AI Criteria-10 (MAIC-10) checklist for artificial intelligence in medical imaging - Jonas M. Getzmann; Kitija Nulle; Cinzia Mennini; Umberto Viglino; Francesca Serpi; Domenico Albano; Carmelo Messina; Stefano Fusco; Salvatore Gitto; Luca Maria Sconfienza (Insights into Imaging)
Abstract Objectives To analyze the methodological quality of studies on deep learning (DL) in rib fracture imaging with the Must AI Criteria-10 (MAIC-10) checklist, and to report insights and experiences regarding the applicability of the MAIC-10 checklist. Materials and methods An electronic literature search was conducted on the PubMed database. After selection of articles, three radiologists independently rated the articles according to MAIC-10. Differences of the MAIC-10 score for each checklist item were assessed using the Fleiss’ kappa coefficient. Results A total of 25 original articles discussing DL applications in rib fracture imaging were identified. Most studies focused on fracture detection (n = 21, 84%). In most of the research papers, internal cross-validation of the dataset was performed (n = 16, 64%), while only six studies (24%) conducted external validation. The mean MAIC-10 score of the 25 studies was 5.63 (SD, 1.84; range 1–8), with the item “clinical need” being reported most consistently (100%) and the item “study design” being most frequently reported incompletely (94.8%). The average inter-rater agreement for the MAIC-10 score was 0.771. Conclusions The MAIC-10 checklist is a valid tool for assessing the quality of AI research in medical imaging with good inter-rater agreement. With regard to rib fracture imaging, items such as “study design”, “explainability”, and “transparency” were often not comprehensively addressed. Critical relevance statement AI in medical imaging has become increasingly common. Therefore, quality control systems of published literature such as the MAIC-10 checklist are needed to ensure high quality research output. Key Points Quality control systems are needed for research on AI in medical imaging. The MAIC-10 checklist is a valid tool to assess AI in medical imaging research quality. Checklist items such as “study design”, “explainability”, and “transparency” are frequently addressed incomprehensively. Graphical Abstract